Space of configurations and the special measures on it - Berezansky, Yu. M. (Methods of Functional Analysis and Topology, 2019)
The article is devoted to an exact account of initial results about configurations and measures on them, starting from the concept of a unique topologization of the space of all configurations, including both finite and infinite cases (not as it is made in the classical works).